Association between the G/G genotype of the lncRNA MEG3 rs7158663 polymorphism and proliferative diabetic retinopathy - Leticia de Almeida Brondani; Isabele Dandolini; Eliandra Girardi; Luís Henrique Canani; Daisy Crispim; Cristine Dieter (Archives of Endocrinology and Metabolism, 2024)
ABSTRACT Objective: To investigate the association between the long noncoding RNAs (lncRNAs) maternally expressed gene 3 (MEG3) rs7158663 polymorphism and diabetic retinopathy (DR) in patients with type 2 diabetes mellitus (T2DM). Subjects and methods: The study included 628 patients with T2DM and DR ("case group," including 283 with proliferative DR [PDR] and 345 with nonproliferative DR [NPDR]), and 381 patients with T2DM but no DR ("control group"). The diagnosis of DR was established using indirect ophthalmoscopy. The rs7158663 A/G polymorphism was genotyped using real-time polymerase chain reaction (PCR) with TaqMan probes. Results: Patients with DR, compared with those without DR, had lower frequencies of both the G/G genotype (17.5% and 23.6%, respectively, p = 0.044) and the G allele (p = 0.017). When only patients with PDR were compared with controls, the G/G genotype was associated with increased protection against PDR after adjustment (odds ratio 0.551, 95% confidence interval 0.314–0.966, p = 0.038). This association also remained in the dominant (p = 0.036) and additive (p = 0.031) genetic models. Conclusion: This study reveals, for the first time, that the G/G genotype of the lncRNA MEG3 rs7158663 single-nucleotide polymorphism is associated with a protective effect against advanced-stage DR in patients with T2DM. Additional studies are warranted to validate this finding.